Bacterial uptake mechanism of peptides investigated by steered molecular dynamics simulations - Akdağ, İhsan Ömür. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2011., 2011)
β-lactam antibiotics provide defense against bacterial infections, but the misuse of antibiotics has led to the emergence of bacteria with immunity. One of the major mechanisms of this immunity is bacterial production of the β-lactamase enzyme which inhibits antibiotics. In order to overcome the inhibition and regain defense against bacteria, development of peptide inhibitors based on β-lactamase inhibitor protein (BLIP) have gained increased attention. The bacterial uptake potential of the designed BLIP based peptide was investigated using steered molecular dynamics simulations. Two peptides were used in the simulations. The BLIP based peptide has the sequence HAAGDYYA. The second peptide is the BLIP based peptide (LLIILHAAGDYYA) with the residues LLIIL added to the N terminus to enhance bacterial uptake. The SMD simulations were repeated with different spring constants, pulling velocities and reaction coordinates to optimize the simulation conditions. It was found that no obvious distinction could be made for different spring constants for the first set, while the second set favored smaller spring constant. The first peptide passed the membrane more easily when it was pulled faster, but the second peptide had shown almost no difference. When both peptides were pulled from their N terminus, the force applied to and the work done on the peptides reached their maximum values. A third set of simulations were performed on the cell penetrating peptide pVEC (LLIILRRRIRKQAHAHSK) and its mutants to analyze their cellular uptake mechanism on a residue basis. Previously the independent mutations on the 1st, 2nd and 14th residues, and scrambling and reversing the sequence of the pVEC peptide found to make the cellular uptake harder. However, the simulations showed that scrambling the sequence , mutation of the 14th, the 1st and the 2nd residues enhanced the uptake in descending order.
Keywords: Beta lactamases.; Beta lactam antibiotics.; Microbiology.